The association between perceived maternal and paternal psychopathology and depression and anxiety symptoms in adolescent girls - Rasing, Sanne P. A.; Creemers, Daan H. M.; Janssens, Jan M. A. M.; Scholte, Ron H. J. (Frontiers in Psychology, 2015)
Exposure to parental depression and anxiety is known to heighten the risk of internalizing symptoms and disorders in children and adolescents. Ample research has focused on the influence of maternal depression and anxiety, but the contribution of psychopathology in fathers remains unclear. We studied the relationships of perceived maternal and paternal psychopathology with adolescents’ depression and anxiety symptoms in a general population sample of 862 adolescent girls (age M = 12.39, SD = .79). Assessments included adolescents’ self-reports of their own depression and anxiety as well as their reports of maternal and paternal psychopathology. We found that perceived maternal and paternal psychopathology were both related to depression and anxiety symptoms in adolescent girls. A combination of higher maternal and paternal psychopathology was related to even higher levels of depression and anxiety in adolescent girls. Our findings showed that adolescents’ perceptions of their parents’ psychopathology are significantly related to their own emotional problems.